Odyssey-ProcessCase: A Case-Based Software Process Line Approach - Costa, Diogo Matheus; Teixeira, Eldânae Nogueira; Werner, Cláudia Maria Lima (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software processes have been the focus of discussion in the literature, but defining a software process that meets project-specific needs remains a challenge. The Software Process Line (SPrL) technique offers a systematic to identify processes' similarities and variability to support software process reuse. Based on a literature review analysis, a concentration of SPrL approaches that use mapping/rules techniques to support project-specific software process definition was observed. However, the knowledge acquisition process required by this kind of technique is not trivial, due to the unavailability of experts and overhead in domain engineering. This paper presents an incremental learning approach for SPrL, called Odyssey-ProcessCase, focused on the decision-making support to solve SPrL variability during the project-specific software process definition. The approach applies techniques such as Case-Based Reasoning (CBR) and Rule-Based System to offer complementary mechanisms to support the decision-making task aiming at the software process definition from reusable artifacts of SPrL.